Aktivitas Antihiperglikemik, Penghambatan Stres Oksidatif, dan Regenerasi Sel ? Pankreas dari Ekstrak Etanol Fraksi-Fraksi Daun Kelakai (Stenochlaena palutris) pada Tikus yang Diinduksi STZ-NA - Efendi, Harun; Billi, Joseph; Citra Jaluri, Poppy Dwi; Sobirin, Miftachul; Muzaroh, Silvia Lutvia; Debora, Shandy (Jurnal Borneo Cendekia, 2025)
Type 2 diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia and oxidative stress, leading to pancreatic ?-cell damage. Kelakai leaves (Stenochlaena palutris) contain bioactive compounds with potential antidiabetic effects. This study aimed to evaluate the antihyperglycemic activity, antioxidant effects, and ?-cell regeneration of ethanol extract and fractions of kelakai leaves in STZ-NA-induced rats. Methods: Ethanol extract of kelakai leaves was fractionated into n-hexane, ethyl acetate, and water fractions. Male Wistar rats were divided into 7 groups (n=6): healthy control, negative control (STZ-NA), positive control (glibenclamide), and treatment groups with extract or fractions. Blood glucose levels were measured on days 0, 7, and 14. Antioxidant parameters (MDA and SOD) were analyzed using commercial kits. ?-cell regeneration was assessed via pancreatic histopathology.Results: Administration of ethanol extract and fractions significantly reduced blood glucose (p<0.05), enhanced antioxidant activity (decreased MDA, increased SOD, CAT, GSH), and improved pancreatic ?-cell histology. The ethyl acetate fraction exhibited the best effects across all parameters. Conclusion: Ethanol extract and fractions of kelakai leaves possess antihyperglycemic and antioxidant properties and support pancreatic ?-cell regeneration in type 2 diabetic rats.